2023
DOI: 10.3390/polym15214235
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Production of Lactic Acid from Cellulose Using Au/W-ZnO Catalysts

Mingyu Guo,
Chengfeng Zhou,
Yuandong Cui
et al.

Abstract: The catalytic conversion of cellulose to lactic acid (LA) has garnered significant attention in recent years due to the potential of cellulose as a renewable and sustainable biomass feedstock. Here, a series of Au/W-ZnO catalysts were synthesized and employed to transform cellulose into LA. Through the optimization of reaction parameters and catalyst compositions, we achieved complete cellulose conversion with a selectivity of 54.6% toward LA over Au/W-ZnO at 245 °C for 4 h. This catalyst system also proved ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Therefore, chemical catalysis strategies have been attempted for the production of lactic acid from sugars or biomass-derivatives with the homogeneous or heterogeneous catalysts. [14][15][16][17][18][19][20][21][22] Wang et al, reported that in the presence of dilute lead (II) ions, glucose was converted to lactic acid at 190 °C with a yield of 66 %. However, the toxicity of lead ions affects the practical application of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, chemical catalysis strategies have been attempted for the production of lactic acid from sugars or biomass-derivatives with the homogeneous or heterogeneous catalysts. [14][15][16][17][18][19][20][21][22] Wang et al, reported that in the presence of dilute lead (II) ions, glucose was converted to lactic acid at 190 °C with a yield of 66 %. However, the toxicity of lead ions affects the practical application of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with bio-fermentation, the catalytic approach for producing LA exhibits greater potential for large-scale production and higher production efficiency. 13–15 Consequently, the catalytic method seems to be a more favorable route for LA production. Various types of catalysts including homogeneous metal-based Lewis acids such as SnCl 2 , 16 SnCl 4 , 17 CrCl 2 , 18 CrCl 3 , 18 Cr 2 (SO 4 ) 3 , 18 alkali hydroxides Ba(OH) 2 , 7 and heterogeneous ( e.g.…”
mentioning
confidence: 99%